Combination of cadherin-17 and SATB homeobox 2 serves as potential optimal makers for the differential diagnosis of pulmonary enteric adenocarcinoma and metastatic colorectal adenocarcinoma - Bian, Tingting (Oncotarget, 2017)
BACKGROUND: Pulmonary enteric adenocarcinoma (PEAC), a rare type of non-small cell lung cancer, has similar histological and immunohistochemical morphology to colorectal adenocarcinoma. Cadherin-17 (CDH17) and SATB homeobox 2 (SATB2) immunoexpression have recently been demonstrated in colorectal adenocarcinoma. In this study, we evaluated the value of CDH17 and SATB2 in the diagnosis of pulmonary enteric adenocarcinoma and metastatic colorectal adenocarcinoma. METHODS: A total of 13 PEAC cases and 27 metastatic colorectal adenocarcinoma cases were enrolled in our cohort study. We analyzed the expressions of CK7, CK20, CDX-2, villin, cadherin-17 (CDH17), and SATB homeobox 2 (SATB2) using immunohistochemistry. Staining intensity and percentage of positive-staining cells were recorded. Sensitivity and specificity values for immunostains, individually and in combination, were computed and compared. RESULTS: Combining CDH17 and SATB2 resulted in high sensitivity (76.92%) and specificity (100%). In our study, the use of CK7+, napsin A+, TTF-1+, napsin A+TTF-1+ in combination with CDH17-/SATB2- had a higher area under the curve compared to the combination CDH17-/SATB2-. However, no significant differences were observed between the combination CDH17-/SATB2- and other combinations (P>0.05). CONCLUSIONS: In combination, CDH17 and SATB2 serve as potential optimal markers for the differential diagnosis of PEAC and metastatic colorectal adenocarcinoma.